1983
DOI: 10.1016/0035-9203(83)90195-5
|View full text |Cite
|
Sign up to set email alerts
|

The use of dexamethasone in preventing ocular complications in tuberculous meningitis

Abstract: Twenty-seven patients with tuberculous meningitis (TBM) were treated with ethambutol, isonicotinic acid hydrazide, streptomycin and dexamethasone and 28 were treated with triple anti-tuberculous drugs only. Only two of the patients to whom steroids were given developed ocular complications as compared to seven of those not receiving dexamethasone. High dose dexamethasone apparently prevents optic atrophy in TBM. Controlled double-blind studies with and without dexamethasone are needed to confirm this postulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…No trial demonstrated significantly worse outcomes with the use of adjunctive corticosteroids in patients with tuberculous meningitis. In fact, the data suggested earlier clinical improvement [33,40], fewer neurologic sequelae [33,[38][39][40][41], and improved survival [34,37,39,41]. These benefits may be most likely observed in patients with spinal block, as well as in patients with intermediate-stage disease, as evidenced by two of the trials [34,39] that stratified patients by disease severity on study entry.…”
Section: Adjunctive Medical Therapiesmentioning
confidence: 91%
See 1 more Smart Citation
“…No trial demonstrated significantly worse outcomes with the use of adjunctive corticosteroids in patients with tuberculous meningitis. In fact, the data suggested earlier clinical improvement [33,40], fewer neurologic sequelae [33,[38][39][40][41], and improved survival [34,37,39,41]. These benefits may be most likely observed in patients with spinal block, as well as in patients with intermediate-stage disease, as evidenced by two of the trials [34,39] that stratified patients by disease severity on study entry.…”
Section: Adjunctive Medical Therapiesmentioning
confidence: 91%
“…By far, most studies have evaluated the use of corticosteroids, since persistent central nervous system inflammation despite antimicrobial therapy is often responsible for the increased morbidity and mortality that is observed in patients with tuberculous meningitis [1,32]. To date, there have been nine controlled trials (resulting in 10 papers) that have examined the role of adjunctive corticosteroids in the treatment of tuberculous meningitis (Table 4) [33][34][35][36][37][38][39][40][41][42]. These trials differed in the severity of illness in the patients studied, patient age, the dose and form of corticosteroid used, and the outcomes analyzed.…”
Section: Adjunctive Medical Therapiesmentioning
confidence: 99%
“…No trial demonstrated significantly worse outcomes with the use of adjunctive corticosteroids in patients with TBM. In fact, most data suggested earlier clinical improvement [35,42], fewer neurologic sequelae [35,[40][41][42]44], and/or improved survival [36,39,41,44,46].…”
Section: Adjunctive Therapiesmentioning
confidence: 99%
“…By far, most studies have evaluated the use of corticosteroids, because persistent CNS inflammation despite antimicrobial therapy is believed to be responsible for much of the increased morbidity and mortality observed in patients with TBM [1]. To date, 12 controlled trials have examined the role of adjunctive corticosteroids in the treatment of TBM (Table 2) [35][36][37][38][39][40][41][42][43][44][45][46]. These trials differ in the severity of illness of the patients studied, patient age, outcomes analyzed, and the dose, form, and duration of corticosteroid therapy.…”
Section: Adjunctive Therapiesmentioning
confidence: 99%
“…The role of adjunctive corticosteroid therapy in the treatment of TB meningitis has been investigated by numerous studies [52][53][54][55][56][57][58][59][60][61][62][63][64], and the updated systematic review conducted in support of the guidelines showed a mortality benefit from the use of adjuvant corticosteroids. Therefore, the guidelines recommend adjunctive corticosteroid therapy with dexamethasone or prednisolone tapered over 6-8 weeks for patients with TB meningitis (PICO question 8).…”
Section: Tb Meningitismentioning
confidence: 99%